Sensitivity Analysis of a Cold Standby System with Priority for Preventive Maintenance: Optimizing system maintenance with sensitivity analysis (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper analyzes sensitivity analysis of a cold standby system with priority for preventive maintenance consist two identical units with server failure using Regenerative Point Graphical Technique (RPGT). In this present paper there are two units one of which is online while other is kept in cold standby mode. Online cold standby unit are indistinguishable in nature and have just two modes one is full limit and second is totally finished failure. There is single repair facility which is available. Taking Repair rates and Failure rates are constant. A state chart of the framework delineating the transition rates is drawn. Sensitive analysis of framework is done which might be helpful to management in keeping up the different units of system Tables figures are set up to look at and draw the conclusion.